Open-Source Intelligence (OSINT) Tools for Law Enforcement - Ramadhany, Gilang Perdana (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This paper aims to provide an overview of the main findings and conclusions of the research conducted. Within the complex and diverse domain of cyberspace, law enforcement authorities are faced with the increasingly difficult task of addressing the growing difficulties presented by highly skilled cyber adversaries. Open Source Intelligence (OSINT) tools have become essential instruments in the cybernetic battleground since they leverage the extensive pool of publicly accessible digital information. This study conducts a comprehensive analysis of the technical functionalities, versatility, and strategic significance of several Open Source Intelligence (OSINT) tools in enhancing the proactive and reactive approaches of law enforcement agencies in countering cyber threats. This study aims to provide a comprehensive understanding of the significant impact of OSINT tools on many aspects of digital forensics, threat intelligence gathering, and predictive analytics. It achieves this by combining quantitative analyses with real-world application scenarios. The empirical findings presented in this study highlight the utmost importance of these technologies in enabling a more comprehensive, evidence-based, and proactive strategy for preventing cybercrime. With the growing complexity of the digital threat landscape, the integration of Open Source Intelligence (OSINT) tools into law enforcement's repertoire becomes vital. This integration provides a promising solution for effectively traversing hazardous cyber terrains.